Venous thromboembolism and bleeding after total knee and hip arthroplasty - Guijarro, Ricardo; Montes, Julio; Roman, Carlos San; Arcelus, Juan Ignacio; Barillari, Giovanni; Granero, Xavier; Monreal, Manuel (Thrombosis and Haemostasis, 2011)
The impact of venous thromboembolism (VTE) and bleeding in patients undergoing major joint surgery has not been thoroughly studied. The Spanish National Discharge Database during the years 2005–2006 was used to assess the frequency and clinical impact of VTE and bleeding after elective total knee (TKA) or hip (THA) arthroplasty. Of 58,037 patients undergoing TKA, 0.18% (95% confidence interval [CI]: 0.15–0.22) were diagnosed with pulmonary embolism (PE), 0.57% (95% CI: 0.51–0.63) with deep-vein thrombosis (DVT), 1.20% (95% CI: 1.12–1.30) had bleeding complications, and 0.09% (95% CI: 0.07–0.12) died. Of 54 patients who died, 20.4% (95% CI: 10.7–35.4) had been diagnosed with PE, 3.70% (95% CI: 0.63–11.7) with DVT, and 13.0% (95% CI: 5.67–25.6) had bled. Of 31,769 patients undergoing elective THA, 0.23% (95% CI: 0.18–0.29) were diagnosed with PE, 0.44% (95% CI: 0.37–0.52) with DVT, 1.21% (95% CI: 1.10–1.34) bled, and 0.16% (95% CI: 0.12–0.21) died. Of 52 patients who died, 13.5% (95% CI: 6.08–24.8) had been diagnosed with PE, and 9.61% (95% CI: 3.52–21.3) had bled. On multivariable analysis, PE (odds ratio [OR]: 157; 95% CI: 75–328), DVT (OR: 6.3; 95% CI: 1.5–27) and bleeding (OR: 8.5; 95% CI: 3.6–20) were independent predictors for death after TKA. After THA, only PE (OR: 65; 95% CI: 26–160) and bleeding (OR: 6.4; 95% CI: 2.3–17) predicted the risk for death. Bleeding, DVT, and PE, arising after TKA were all independent predictors for death. Their increase in risk was, however, substantially higher for PE. After THA, only PE and bleeding independently predicted death.
Keywords: Prophylaxis; surgery; orthopaedics; venous thrombosis; pulmonary embolism